Capnocytophaga Keratitis: Clinical Presentation and Use of Metagenomic Deep Sequencing for Diagnosis. Issue 2 (February 2019) - Seitzman, Gerami D.; Thulasi, Praneetha; Hinterwirth, Armin; Chen, Cindi; Shantha, Jessica; Doan, Thuy
Abstract : Purpose: To report our experience with 2 cases of Capnocytophaga keratitis. Methods: This is a retrospective study of case reports. We present the clinical presentation, diagnosis, and treatment strategies of 2 patients who presented with Capnocytophaga keratitis. Results: Both patients had risk factors including systemic immune compromise and ocular trauma. Both patients had robust inflammatory keratitis with necrosis. Case 1 demonstrates identification of Capnocytophaga with traditional microbiologic techniques. Case 2 demonstrates the use of unbiased metagenomic deep sequencing for identification of this unusual corneal pathogen. Conclusions: Capnocytophaga is a rare and aggressive infection. Even when traditional culture identifies the pathogen rapidly, keratitis can progress to perforation. In cases of severe keratitis in which traditional culture methods are unrevealing, metagenomic deep sequencing has potential to provide actionable diagnoses.